A protean relationship: literature and philosophy - Jiménez, Mauro (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Presentación.
Keywords: Literature; Philosophy; Theory of Literature; Comparative Literature; Interdiscursivity